OS PROCESSOS COMUNICACIONAIS DO MOVIMENTO PUNK NA DITADURA MILITAR - SOUZA, RENAN MARCHESINI DE QUADROS (2017)
This research aims to think about the cultural impacts of the punk movement in São Paulo, through the final period of the military dictatorship (1977 - 1985). Looking to identify under which communication forms, the movement used to spread and fight for his ideals, in a period when they were repressed furiously. Debating the history of the punk movement in the world and his repercussion and, specifically, his development in São Paulo and the ABC area. Whereas the cultural impacts the movement had in the Brazilian and São Paulo society, the ways of resistance they applied, as like possible clashes that had been stablished with the militaries and the hegemonic culture at the period. For this discussion were used as references theorists, the cultural studies, the semiotic of culture, the theories of social movements and the musical literature, with focus the punk rock. This research can/may identify the value of the cultural production of the punk movement using the model do it yourself, just as its significances while a set of communication process that counterpoint to the hegemonic culture impose at the period